Interfaces formativas da educação do campo e do desenvolvimento rural sustentável à jovens de colégios agrícolas nos municípios de Toledo e Palotina - Paraná - Sbaraini, Ramony Dafne (2019)
This study presents a look on the education of the field by the reality of the Agricultural Colleges located in the cities of Toledo and Palotina - Paraná. Its theoretical basis runs through the themes of rural education, as well as the policies that underpin them; the Environmental Education and Sustainability aspect, presenting education as a tool for sustainable development; Educational policies that encompass environmental education; The relation of interdisciplinarity; The theme of rural youth and agricultural technical education, focusing on youth and the right to sustainability and the environment in the countryside and the protagonism of the rural youth. This study is characterized as exploratory and descriptive, using qualitative and quantitative methods of analysis, based on bibliographic research. The technique of analysis and data collection occurred through group interactions, corresponding to focal groups (GP). How do the agricultural colleges of the West of Paraná develop the fundamentals of rural education? If there is an interrelation with environmental education and sustainable rural development, and if young people identify the relevance of this interface? The Research was submitted to the Ethics Committee in Research Involving Human Beings of UNIOESTE – Universidade Estadual do Oeste Paraná and approved on April 9, 2018. This study was based on the documentary perspective of the Political Educational Project (PPP); the Curricular Pedagogical Proposal (PPC); faculty and students of the two colleges analyzed. It can be identified at various points analyzed, both in theory and in practice, that the colleges follow the proposed goal of promoting agroecological sustainability, and seek to raise awareness of the development of family agriculture and the environment through educational actions and processes oriented to environmental education. I emphasize in this work that the importance in relation to the field is not only in the rural exodus, but in the protagonism of the rural youth, in the awakening of the care for the environment, in the search for sustainable rural development. And that technical education has the role of contributing to the construction of young transformers and influencers of change. It was observed that the labor market of the region where the colleges are inserted has a strong impact on agribusiness, leading to imposition so that the agricultural technical education of the region analyzed turns to the education of rural education and not the field. This fact generates one of the great challenges to be faced, which is to fight for the education of the field, so that it occurs with quality, following its principles. Thus, the importance of studies that involve their participation in the rural environment and the interference with sustainable rural development.